Ecchymosis evaluation after internal and external continuous lateral nasal osteotomy in open rhinoplasty - Felipe Pimentel Magno; Henrique Biavatti; Juliana Bolandini de Matos; Bruno Perrelli Sá Freire Fernandes; Felipe Gomes de Oliveira Queiroga; Bianca Maria Barros Ohana; Celso Eduardo Jandre Boechat (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: The objective is to evaluate the presence of ecchymosis 7 and 15 days after internal and external lateral nasal osteotomy in open rhinoplasty. Methods: A prospective evaluation of 15 patients who underwent open rhinoplasty with lateral nasal osteotomy was conducted. The patients were allocated into two groups. Those who underwent external lateral nasal osteotomy were included in group A (n = 6), while those who underwent internal osteotomy were included in group B (n = 9). The patients were evaluated on postoperative days 7 and 15, and the presence or absence of ecchymosis was recorded. Results: In group A, we observed that on postoperative day 7, 3 patients (50%) had ecchymosis and 3 (50%) showed no changes in skin color. On postoperative day 15, the same group had 2 patients (25%) with ecchymosis and 4 (75%) without changes. On the other hand, in group B, 3 patients (33.4%) had ecchymosis and 6 (66.6%) showed no changes on postoperative day 7. In the same group, 1 patient (11.1%) had ecchymosis and 8 (88.9%) showed no changes 15 days after surgery. Conclusion: Despite the lower incidence of ecchymosis in internal fractures on postoperative days 7 and 15, no statistical significance was observed between the two techniques.